Herschend Enterprises : unifying and communicating the voice of ownership - Craig, Justin B.; Pendergast, Jennifer M.; Waikar, Sachin (London : Publisher as Kellogg School of Management, 2021)
This case features a family business working to better integrate the voice of the whole family into corporate governance. In November 2019, the Herschend Enterprises board prepared to elect its first family chair in almost 20 years. For several years, the business, which owned and operated multiple popular US-based theme parks and other entertainment offerings, had been governed by a majority independent board led by an independent chair and run by a non-family CEO, with an engaged but largely hands-off family ownership group. Third- and fourth-generation owners struggled with how best to provide input on company direction. This was partly because several longtime independent directors, who were deeply trusted by the family and knew the business very well, were able to shape decisions and wield influence with minimal family input.In this context, the family had recently formed an owners' council responsible for consolidating the owners' voice. But the inaugural council members recognized that family leadership in general remained concentrated among a few members who filled slots on the family council, owners' council, and board. The company therefore had no effective mechanism in place to consolidate the voice of the owners and assure this was heard in the boardroom. Instead, it relied on the individual voices of owners who reached out to independent directors or on owners who already served as family directors.Grappling with these challenges were third- and fourth-generation family and owners' council members Chris (the incoming board chair), Jim, Jonn, and Austin Herschend-all serving or former Herschend corporate board directors. They considered how best to unify and engage the family around issues such as advising and working with the board, engagement of the broad ownership group, determination of optimal profiles for owners' council members and family directors, and the looming decision of moving from an independent chair to a family chair.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Family-owned business enterprises -- Case studies; Corporate governance -- Case studies